Everolimus eluting bioresorbable vascular scaffolds in patients with acute coronary syndromes: Two-year results from the German-Austrian ABSORB registry - Tröbs, Monique; Achenbach, Stephan; Nef, Holger M.; Gori, Tomasso; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Woehrle, Jochen; Zahn, Ralf; Hamm, Christian W. (Catheterization and Cardiovascular Interventions, 2021)
Objectives To identify potential differences in 2-year outcome between patients who underwent coronary revascularization using bioresorbable vascular scafffolds (BVS) in stable coronary artery disease (CAD) and acute coronary syndromes (ACS).
CRIS-Team WoS Importer:2021-07-02